The case for global discontent (Perspectives on Global Development 2021, 2021)
This chapter examines the rise in discontent evident since the global financial crisis. It analyses protests and other forms of civil unrest across the world with a view to understanding where these events are most common and who is most likely to be involved. It also studies other political indicators with particular relevance to democratic systems of government: trust in government, voter turnout and support for democracy. The chapter then explores the contingent causes of discontent with reference to public attitude surveys from different regions. These shed light on citizens’ principal worries and frustrations as they relate to the state of the economy and the quality of public goods. It also analyses the extent to which citizens feel they have a say in how their country is run.